Cytotoxicity of selected pyridinium oximes in human SH-SY5Y neuroblastoma cell line - Kalanj Bognar, Svjetlana (Array, 2008)
Summary: Pyridinium oximes are pharmacologically important nucleophylic agents acting as effective antidotes against poisoning by organophosphorus compounds that inhibit acetylcholinesterase (AChE; EC 3.1.1.7.). In this study, the cytotoxicity of 1-phenacylpyridinium-4-aldoxime chloride (FEPA-4) was analyzed in human SH-SY5Y neuroblastoma cell line highly expressing acetylcholinesterase. The concentrations of 0.5, 1, 2 and 4 mmol dm–3 and time-dependent effects at 1, 3, 6, 12 and 24 hours were tested in comparison with non-treated cells. In addition, neuroblastoma cells were treated with a well known antidote 1,1'-bis(pyridinium-4-aldoxime)trimethylene dibromide (TMB-4) at the concentration of 0.8 mmol dm–3, the highest studied concentration which in several non-neural cellular models induced no cytotoxicity. Cytotoxic effects i.e. altered cellular morphology and decreased cellular volume density quantified by stereological method were observed in FEPA-4 treated cells, while no cytotoxic effect was observed for 0.8 mmol dm–3 TMB-4. Possible mechanisms of observed FEPA-4 cytotoxicity in neuroblastoma cells are discussed